EFEKTIVITAS PENERAPAN IZIN KERJA KHUSUS RUANG TERBATAS PADA PENGELASAN TANKI UTAMA FUEL TRUCK DI PT. MANGGALA USAHA MANUNGGAL KUTAI TIMUR - Rusba , Komeyni; Zain, Abdul; Siboro, Impol1; Sanjaya, Rahmat (Program Studi Kesehatan dan Keselamatan Kerja, 2023)
This study aims to describe the effectiveness of the application of a confined space special work permit procedure for welding the main tank of the fuel truck at PT. Mangala Usaha Manunggal. Confined space has a very high potential hazard that can endanger the safety of someone who enters it, so prevention efforts are needed to avoid work accidents, one of which is the application of a special work permit to work in a confined space. This type of research is descriptive research with qualitative methods. Data collection was done through observation and interviews. Informants in this study consisted of: 1 head of the HSE department, 1 HSE executive, 1 head of the PLANT department, and 1 work supervisor. Data analysis based on KEP No. 113/DJPPK/IX/2006, and SOP-00-HSE-008 special work permit for PT. Mangala Usaha Manunggal. The process of working in confined spaces includes the implementation of procedures for the confined spaces system in which every work in a confined space must have a person in charge, working employees, stand-by person and safety officer who gives permission to work in the confined spaces area. The results of this study indicate that the amount of conformity between regulatory standards and existing conditions at the work preparation stage is 86%, at the work implementation stage is 81%, at the closing/completed work stage is 100%, then the overall value obtained is 89% so that these results indicate the level of achievement in the level of effectiveness included in the criteria of